Knowledge of, and Attitudes Towards Health-related Biotechnology Applications Amongst Australian Year 10 High School Students. Issue 3 (2nd July 2016) - van Lieshout, Emile; Dawson, Vaille
Abstract : Modern biotechnology has a large and rapidly increasing impact on society. New advances in genetics, stem cells and other areas hold great potential for human health but also presenting socioscientific issues that commonly divide public opinion. While knowledge is necessary to develop informed opinions about biotechnology, they may also be influenced by polarized discourse and fiction in the media. Here, we examined prior knowledge about and attitudes towards health-related biotechnological applications in Year 10 high school students from Western Australia using online questionnaires. The impact of teaching on students' understanding was tested by repeating the questionnaire after a lesson. Finally, students' argumentation skills were examined by recording responses to statements about biotechnological applications. We found that, prior to instruction, most students exhibited a reasonable understanding of biotechnology. There was little evidence for alternative conceptions, and instruction led to a diversification in understanding. Attitudes towards biotechnology were generally positive but varied. Despite interest in biotechnological issues, argument for positions was generally cognitive-affective in nature. Consequently, biotechnology is a relevant topic for science education, and presents excellent opportunities to build on pre-existing knowledge. Rather than expanding students' knowledge, our results suggest educators should focus on deepening existing understanding and strengthening argumentation skills.